Religious Education for Plural Societies: The Selected Works of Robert Jackson - Jackson, Robert (Routledge, 2018)
Cover -- Half Title -- Title Page -- Copyright Page -- Table of Contents -- Foreword -- Acknowledgements -- PART I: General introduction -- My work in the context of debates about religious education -- Changes in religious education in the UK, Europe and internationally -- Key influences: secularisation, pluralisation and globalisation -- Educational encounters with religious diversity -- Inclusive religious education: information-based, neutral and detached and information-based impartial and dialogical approaches -- Faith-based and impartial religious education -- Recent developments -- The present volume -- Notes -- References -- 1. Religious education and the arts of interpretation revisited -- Introduction -- Teacher training and teaching -- Teacher-trainer, philosophy and 'world religions' -- Broadcasting and field research -- Learning and creativity -- Past, present and future -- References -- PART II: Empirical research -- Introduction -- The chapters -- Note -- References -- 2. Studying British Hindu children and representing them in school texts -- Hindus in Britain -- Religious practice -- Religious transmission -- Some findings -- Multiple cultural competence -- Religions Through Festivals: Hinduism -- Listening to Hindus -- References -- 3. The diversity of experience in the religious upbringing of children from Christian families in Britain -- Ethnic diversity -- Denominational and doctrinal diversity -- The Holy Spirit -- Baptism -- Holy Communion -- Saints -- Conclusion -- Being a Christian at school -- Notes -- References -- 4. The 'Young People's Attitudes to Religious Diversity' project in the context of Warwick Religions and Education Research Unit (WRERU) research -- WRERU's studies of religious diversity and education -- Expansion of WRERU and the UK government DCSF project